2015
DOI: 10.1155/2015/504251
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Antimagicness of Disconnected Graphs

Abstract: A simple graphGadmits anH-covering if every edge inE(G)belongs to a subgraph ofGisomorphic toH. The graphGis said to be (a,d)-H-antimagic if there exists a bijection from the vertex setV(G)and the edge setE(G)onto the set of integers1, 2, …,VG+E(G)such that, for all subgraphsH′ofGisomorphic toH, the sum of labels of all vertices and edges belonging toH′constitute the arithmetic progression with the initial termaand the common differenced.Gis said to be a super (a,d)-H-antimagic if the smallest possible labels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…If p = n − 1 then the graph St n−1 n contains n + 1 subgraphs isomorphic to S n . We denote them {S 1 n , S 2 n , . .…”
Section: Super Star-antimagic Graphsmentioning
confidence: 99%
“…If p = n − 1 then the graph St n−1 n contains n + 1 subgraphs isomorphic to S n . We denote them {S 1 n , S 2 n , . .…”
Section: Super Star-antimagic Graphsmentioning
confidence: 99%
“…The existence of super (a, d)-H-antimagic labelings for disconnected graphs is studied in [7]. In [4] it is shown that the disjoint union of multiple copies of a (super) (a, 1)-treeantimagic graph is also a (super) (b, 1)-tree-antimagic. This leads to a natural question.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], Gutiérrez and Lladó defined Q-supermagic labelings and the results: P n and C n which are P h -supermagic for some h were proved. Lladó and Moragas [2] investigated C h -magicness of wheels W n , windmills W(n, r), books B n , and of prisms D n for some h. In [3], Baca et al proved results for tree-antimagicness of disconnected graphs. Noshad Ali et al in [4] discussed the C 3 -antimagicness of corona graphs.…”
Section: Introductionmentioning
confidence: 99%